Bushido Pada Masyarakat Jepang : Masa Lalu dan Masa Kini - Titiek Suliyati (Universitas Diponegoro, 2013)
ABSTRACT Special characteristic of every nation is influenced by each geographical invironment, and outside elements. Japanese nation is one of nations that has unique culture values that still exist. Japanese culture values influence mainset in their live from the past until the present. This mainset evokes awareness that Western domination can not be defeated by arms only ,but also by the spirit of bushido. The spirit of bushido can not be separated from Samurai imerged in Kamakura period (1192 -1333). Bushido is the principal and way of life that constitutes honesty, bravery, generousity, politesness, honour, dignity, faithfulness, responsibility, self control etc. This awareness leads to the edvancement in technogy and industry of Japanese nation.Because of its long existence of Samurai (1192-1912), the spririt of bushido resides in Japanese character and personality . Keyword : Bushido, Samurai, Japanese Culture